Short-Term Outcomes of Totally Extraperitoneal and Extended Totally Extraperitoneal Repair of Ventral Hernia - Thorat, Santosh D.; Bilaskar, Rajeev P. (Lietuvos chirurgija, 2024)
Since the beginning of surgical history, treatment of hernia has evolved through different stages. Belyansky et al. reported that this technique of e-TEP can also be applied for ventral hernia repair in 2017. The retro muscular e-TEP/e-RS approach combines the advantages of the sublay position of the mesh along with the benefits of the minimal invasiveness of the procedure. A prospective observational study was conducted among 60 patients with non-complicated ventral hernia who were randomised into two groups, equally, who were further subjected to either TEP or e-TEP laparoscopic ventral hernia repair. Distribution of median duration of surgery for among the cases studied was significantly higher in Laparoscopic e-TEP repair group as compared to Laparoscopic TEP repair group. e-TEP has advantage over TEP owing to less steeper learning curve, with wide angle view, more degree of movements for instruments, and ergonomically better operative experience.